2019
DOI: 10.1186/s40169-019-0227-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fatty acid binding protein 5‐deficiency on COPD exacerbations and cigarette smoke‐induced inflammatory response to bacterial infection

Abstract: BackgroundAlthough cigarette smoking (CS) is by far the most important risk factor of chronic obstructive pulmonary disease (COPD), repeated and sustained infections are clearly linked to disease pathogenesis and are responsible for acute inflammatory flares (i.e. COPD exacerbations). We have previously identified Fatty Acid Binding Protein 5 (FABP5) as an important anti‐inflammatory protein in primary airway epithelial cells. ResultsIn this study we found decreased FABP5 mRNA and protein levels in peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…FABP5 is involved in the pathogenesis of viral/bacterial lung infection and the airway inflammation in allergic asthmatics 15 , 16 , 22 . To evaluate the precise role of FABP5 in allergic lung inflammation, we intranasally administrated recombinant IL-33, one of the cytokines known to cause lung inflammation through ILC2 activation, into mice and examined lung inflammation in wild-type and Fabp5 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FABP5 is involved in the pathogenesis of viral/bacterial lung infection and the airway inflammation in allergic asthmatics 15 , 16 , 22 . To evaluate the precise role of FABP5 in allergic lung inflammation, we intranasally administrated recombinant IL-33, one of the cytokines known to cause lung inflammation through ILC2 activation, into mice and examined lung inflammation in wild-type and Fabp5 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…FABP5 in alveolar epithelial cells is responsible for RA synthesis during allergic lung inflammation. As mentioned above, FABP5 is expressed on a variety of lung cells [15][16][17] . Immunostaining with EpCAM or CD11c and FABP5 showed that the FABP5 + cells overlapped with the EpCAM + or CD11c + cells in lung tissue (Fig.…”
Section: Genementioning
confidence: 94%
“…Fresh lung tissues were homogenized and mixed with 1 ml Trizol reagent for total RNA extraction, which was then reversely transcribed to cDNA using the first-strand cDNA synthesis kit as previously described [24][25][26][27]. The qRT-PCR was performed using SYBR Green Mix and the melting curve analysis was performed to examine the specificity of the primer sequence and amplification.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
“…Researchers have previously reported that COPD patients have dysfunction in pulmonary microvessels. Proteinuria indicates not only damage to microvessels in the kidney but also microvascular dysfunction in pulmonary circulation 38 . The severity of proteinuria is related to the severity of COPD, including pulmonary function 39 .…”
Section: Respiratory Biosamples Utilized In Biomarker Measurementmentioning
confidence: 99%